P439 Effectiveness of Ustekinumab on Crohn's disease associated spondyloartropathy: real-world data from the Sicilian Network for Inflammatory Bowel Diseases (SN-IBD). (27th May 2021) - Macaluso, F; Fries, W; Viola, A; Costantino, G; Muscianisi, M; Cappello, M; Guida, L; Giuffrida, E; Magnano, A; Pluchino, D; Ferracane, C; Magrì, G; et al.
Abstract: Background: The efficacy of Ustekinumab (UST) on Crohn's disease (CD) associated spondyloarthropathy (SpA) was evaluated neither in randomized controlled trials nor in real-world studies. Web-based data from the cohort of the Sicilian Network for Inflammatory Bowel Disease (SN-IBD) were extracted to perform a multicentre, real-world assessment of the effectiveness of UST on CD-associated SpA Methods: All consecutive CD patients with active SpA at the initiation of the treatment with UST from January 2019 (the date on which the drug became available for clinical practice in Sicily) to August 2019 were extracted from the SN-IBD cohort. The study outcomes were evaluated at 8 and 24 weeks. The primary outcome was the articular response, defined as the disappearance of objective signs of arthritis (swelling and/or articular stiffness) and resolution of pain. As ancillary end-points, the clinical response (reduction of Harvey-Bradshaw Index ≥ 3 compared with baseline with a concomitant reduction of at least ≥ 50% of steroid dosage compared with baseline) and the steroid-free remission (Harvey-Bradshaw Index < 5 without steroids use) were assessed. Results: Out of 131 total patients treated with UST, 30 consecutive patients (22.9%) had active SpA at baseline (axial SpA: 3/30; peripheral SpA: 18/30; axial plus peripheral SpA: 9/30). After 8 weeks, 10 patients (33.3%) reported an articular response [0/3 patients with axial SpA, 7/18 patients (38.9%) with peripheral SpA, and 3/9 patients (33.3%) with axial and peripheral SpA]. After 24 weeks, 13 patients (43.3%) had an articular response [0/3 patients with axial SpA, 10/18 patients (55.5%) with peripheral SpA, and 3/9 patients (33.3%) with axial and peripheral SpA]. None of these 13 responders was taking systemic steroids at 24 weeks. The concomitant presence of a clinical response on intestinal symptoms was associated with the articular response at 24 weeks at univariable analysis (OR 5.14, CI 1.09-32.70, p=0.038). Conclusion: UST obtained a response on articular symptoms in nearly half of the patients with CD and active SpA at baseline after 24 weeks. The rate of response was higher in case of peripheral arthropathy. The articular response was associated with the clinical response on intestinal symptoms.